Inovasi Produk Kreatif dari Ecobrik Berbasis Limbah Plastik di Betara Tanjung Jabung Barat - Edwin Permana; Kristina Oktavia Limbong; Fery Ramadhani; Rafael Satriyuda; Nazwa Dwi Putri; Susan Adventri Manullang; Eni Mika Agus Br Nainggolan; Rani Ramadani; Ruben Aditia Gultom; Dimas Setya Nurjamil; Dhian Eka Wijaya; Martina Asti Rahayu; Dicky Satrio (CV. ITTC INDONESIA, 2026)
The waste problem in Indonesia is very dangerous for the environment and health of the Indonesian people. The waste problem is a classic problem that is always faced by residents, especially in the Betara area of ​​West Tanjung Jabung Regency. The problem of plastic waste has several broad and serious negative impacts on the environment and human health. This aims to increase awareness of the Betara community, West Tanjung Jabung Regency, about the benefits of managing plastic waste through recycling into functional ecobricks. the continuity of activities causes changes or activities that have been previously designed. Various programs and activities that have been carried out by the team have target achievements that can provide many benefits for students and local residents.